IMPLEMENTATION OF ASSOCIATION RULES USING APRIPORI ALGORITHM FOR ANGKRINGAN - Lestari, Wiji; Hasanah, Herliyani; Susanto, Rudi (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Angkringan is a culinary business that is often found, especially in Surakarta and Yogyakarta in particular and Central Java in general. Most angkringan include small and medium enterprises (SMES). Food and drink merchandise mapping is an important thing in angkringan. In this research, food and drink mapping was carried out at several snack bars in Jebres sub-district, Surakarta city using word clouds and the Apriori algorithm. The word cloud will produce the dominant food and beverage itemsets which will then be processed using the Apriori algorithm. The results of mapping with the Apriori algorithm for food yield support(tempeh) = support (tofu) = 95 which is the highest. Relationship value between dominant itemsets: Confidence(tempeh, tofuâ†’satay, milkfish rice, quail egg, bakwan) = 21. Results for drinks have the highest support value for tea, support(tea) = 100. Relationship value between dominant itemsets: Confidence(tea â†’ coffee, milk, ginger) = 15.